Perceptions of Public and Nonpublic Reporting of Interventional Cardiology Outcomes and Its Impact on Practice: Insights From the Veterans Affairs Clinical Assessment, Reporting, and Tracking Program. Issue 22 (19th November 2019) - Morrison, Justin; Plomondon, Mary E.; O'Donnell, Colin I.; Giri, Jay; Doll, Jacob A.; Valle, Javier A.; Waldo, Stephen W.
Abstract : Background: Physicians have expressed significant mistrust with public reporting of interventional cardiology outcomes. Similar data are not available on alternative reporting structures, including nonpublic quality improvement programs with internally distributed measures of interventional quality. We thus sought to evaluate the perceptions of public and nonpublic reporting of interventional cardiology outcomes and its impact on clinical practice. Methods and Results: A standardized survey was distributed to 218 interventional cardiologists in the Veterans Affairs Healthcare System, with responses received from 62 (28%). The majority of respondents (90%) expressed some or a great deal of trust in the analytic methods used to generate reports in a nonpublic quality improvement system within Veterans Affairs, while a minority (35%) expressed similar trust in the analytic methods in a public reporting system that operates outside Veterans Affairs ( P <0.001). Similarly, a minority of respondents (44%) felt that in‐hospital and 30‐day mortality accurately reflected interventional quality in a nonpublic quality improvement system, though a smaller proportion of survey participants (15%) felt that the same outcome reflected procedural quality in public reporting systems ( P <0.001). Despite these sentiments, the majority of operators did not feel pressured to avoid (82% and 75%; P =0.383) or perform (72% and 63%; P =0.096) high‐risk procedures within or outside Veterans Affairs. Conclusions: Interventional cardiologists express greater trust in analytic methods and clinical outcomes reported in a nonpublic quality improvement program than external public reporting environments. The majority of physicians did not feel pressured to avoid or perform high‐risk procedures, which may improve access to interventional care among high‐risk patients.